Preferensi Masyarakat Terhadap Ketersediaan Bus Trans Jakarta Sebagai Moda Alternatif - Hayati, Dwi Nur; Barus, Lita (Institut Transportasi dan Logistik Trisakti, 2023)
Halim Perdana Kusuma International Airport has a quite significant increasing number of passengers since it was operated commercially in 2014. The number of passengers in 2018 reached 7,446,544 people of a daily average passengers of 20,685 people. There are some advanced modes available in the airport; conventional taxis, online taxis and a number of bus from Damri. As the international airport located not far from the city center, closely linked to issues of congestion and air pollution, the urban public transportation is one of the solutions to meet people’s mobility needs, including travel to and/or from the airport. This study analyzes that people prefer Trans Jakarta bus infrastructure to be built in the airport as the new alternative mode to support onward travel to and/or from the airport. The data collection was carried out using an online survey and processed using Descriptive analysis method. The results of the research show that 64.8% of the respondents stated that the current advanced modes of transportation in the airport have not fully provided for the community who use them as the alternative modes and 95.8% of the respondents are willing to switch to Trans Jakarta bus when the infrastructure has been built. This study also analyzes the factors could influence respondents’ interests to provide recommendations to formulate the sustainable public transportation modes policies.